The importance of RNA modifications: From cells to muscle physiology. (19th October 2021) - Das, Anindhya Sundar; Alfonzo, Juan D.; Accornero, Federica
Abstract: Naturally occurring post‐transcriptional chemical modifications serve critical roles in impacting RNA structure and function. More directly, modifications may affect RNA stability, intracellular transport, translational efficiency, and fidelity. The combination of effects caused by modifications are ultimately linked to gene expression regulation at a genome‐wide scale. The latter is especially true in systems that undergo rapid metabolic and or translational remodeling in response to external stimuli, such as the presence of stressors, but beyond that, modifications may also affect cell homeostasis. Although examples of the importance of RNA modifications in translation are accumulating rapidly, still what these contribute to the function of complex physiological systems such as muscle is only recently emerging. In the present review, we will introduce key information on various modifications and highlight connections between those and cellular malfunctions. In passing, we will describe well‐documented roles for modifications in the nervous system and use this information as a stepping stone to emphasize a glaring paucity of knowledge on the role of RNA modifications in heart and skeletal muscle, with particular emphasis on mitochondrial function in those systems. This article is categorized under: RNA in Disease and Development > RNA in Disease RNA Processing > RNA Editing and Modification Abstract : RNA‐modification in muscle physiology.